Analisis Pembelian Obat Herbal Terhadap ATP (Ability to Pay) Pembiayaan Secara Mandiri di Masyarakat Wilayah Banjarmasin Utara - Bai Abrar; Melviani Melviani; Angga Irawan (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Background: The division of the economic class of society consisting of upper,middle and lower economic classes, this is the problem and what factors cause it to occur. From observations, it can be seen that the community only purchases medicine if it is in an urgent situation because of illness, not for the long term,such as supplies / reserves. Purpose: Knowing the description of the purchase of herbal Against ATP (Ability To Pay) independent financing in the community of North Banjarmasin Region. Methods: This study used an analytic observational method with a cross sectional design, which was carried out by confinient sampling using a geogle form method in North Banjarmasin District from October to November 2020 totaling 30 people, taken using random sampling technique Data were analyzed by describing the characteristics of each variable using the mean, median and standard deviation values, usually this analysis only produces a frequency distribution and the percentage of each variable. Result: Cost of buying medicine <Rp. 250.000 in a month as many as 18 respondents (60.0%) and respondents who bought medicine> Rp. 250.000 in a month were 12 respondents (40.0%). The average ability to pay the respondent is Rp. 120,666 with the highest ability to pay Rp. 220,000 and the lowest ability to pay Rp. 20,000. As for herbal medicine that people often buy are Antangin JRG (16.7%). Conclusion: Most of society has ability to buy herbal remedies (ability to pay) in moderate categories That is (27.1%) at the cost of public which spending still less rp. < Rp.250.000. Whereas the average society in buying herbal remedies is rp. 171,833 and the average of society’s ability to buy herb medicine is Rp 120,666 so that average society’s ability to buy herb medicines (ability to pay) can Said still low compared with average of income that is Rp.2,720,000 and average of society expense is 1.530.000 in North Banjarmasin area, Banjarmasin.